2007
DOI: 10.1111/j.1939-1676.2007.tb02985.x
|View full text |Cite
|
Sign up to set email alerts
|

Day‐to‐Day Variation of the Urine Protein: Creatinine Ratio in Female Dogs with Stable Glomerular Proteinuria Caused by X‐Linked Hereditary Nephropathy

Abstract: Background: Interpretation of serial urine protein : creatinine (UPC) values is confounded by a lack of data regarding random biologic variation of UPC values in dogs with stable glomerular proteinuria.Hypothesis: That there is minimal day-to-day variability in the UPC of dogs with unchanging proteinuria and the number of measurements needed to reliably estimate UPC varies with the magnitude of proteinuria.Animals: Forty-eight heterozygous (carrier) female dogs with X-linked hereditary nephropathy (XLHN) causi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 21 publications
0
46
0
3
Order By: Relevance
“…When monitoring dogs with proteinuria, it is recommended that the UPC must change by 80% at lower UPC (near 0.5) and by at least 35% at higher UPC (near 12) to be considered clinically relevant . When assessing agreement between single UPC and pooled UPC in our study, we found that single UPC could differ from the pooled UPC by <15 or >51%.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…When monitoring dogs with proteinuria, it is recommended that the UPC must change by 80% at lower UPC (near 0.5) and by at least 35% at higher UPC (near 12) to be considered clinically relevant . When assessing agreement between single UPC and pooled UPC in our study, we found that single UPC could differ from the pooled UPC by <15 or >51%.…”
Section: Discussionmentioning
confidence: 62%
“…If the baseline UPC was 8.0, then depending on the method used, the subsequent UPC could be between 7.83 and 10.4. According to a previous study, this result also would not be considered clinically relevant because the results only differ by 2–30%, respectively. Therefore, the difference in UPC between the 2 methods would be acceptable in dogs with lower or higher UPC results.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In 4 cases (10%), dogs switched to a higher classification on the consecutive sample, not explained by the sediment. There is daily variation in UPC values . To indicate disease progression or adequate treatment response, differences in UPC have to be >80% at a UPC near 0.5 .…”
Section: Discussionmentioning
confidence: 99%
“…There is daily variation in UPC values . To indicate disease progression or adequate treatment response, differences in UPC have to be >80% at a UPC near 0.5 . In the dogs with inconsistent consecutive UPC categories, a variance of >80% was only seen in 1 sample (switching from no proteinuria to overt proteinuria).…”
Section: Discussionmentioning
confidence: 99%